Entry Mode of Firms in an Emerging Economy: Evidence from Malaysia - Yasmeen, Kausar; Viswanathan, Kuperan (International Journal of Economics and Financial Issues, 2016)
The dynamics of the global competition patterns and world economy are encouraging construction firms to expand into emerging economies. Entry modes and its predictors have been the subjects of interest in international market strategic management research which is nonetheless lacking in the construction firms. This paper seeks to identify the entry modes preferred by construction firms in Malaysia, on whether they choose equity modes, non-equity modes or both modes for their international projects. The cross-sectional data was collected by distributing one hundred and nineteen questionnaires; the response rate was fifty three percent. By applying multinomial logit model, this study validates the proposition that entry mode selection in an emerging economy is significantly influenced by situational contingencies at three levels of country-specific factors which are government intervention, property right and environmental uncertainty. Entrepreneurial skill is the predictor of entry mode. The effect of the country-specific factor and entrepreneurial skill on entry mode of construction firms depend on a level of entrepreneurial skill. This study contributes to the international market strategic management choice of entry mode. Keywords: entry mode, firms, country-specific factors, emerging economy JEL Classifications: M, M5, M21